2010
DOI: 10.1108/02635571011008380
|View full text |Cite
|
Sign up to set email alerts
|

Employee empowerment in a technology advanced work environment

Abstract: PurposeThe purpose of this paper is to elicit the determinants of information technology (IT) professional work change and investigates the impact of such changes on IT professionals. Specifically, this paper investigates the effect of work redesign on two personal outcomes: self‐perceived psychological empowerment and organizational commitment.Design/methodology/approachAn empirical study is conducted in the field of high‐tech industrial organizations in Taiwan. Data collected from 40 technological companies,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
21
0
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 61 publications
6
21
0
5
Order By: Relevance
“…In a study conducted by Joo & Shim (2010), empowerment practices had a positive influence on organizational commitment, and in another study of 40 technology companies in Taiwan, Kuo et al (2010) have shown similar results linking empowerment and organizational commitment. Similarly, Yang (2011) in his study conducted on a sample of 172 restaurant employees in Taiwan revealed that HRM practices tell that empowerment was positively and directly related to affective commitment.…”
Section: E Empowerment and Organizational Commitmentsupporting
confidence: 48%
See 2 more Smart Citations
“…In a study conducted by Joo & Shim (2010), empowerment practices had a positive influence on organizational commitment, and in another study of 40 technology companies in Taiwan, Kuo et al (2010) have shown similar results linking empowerment and organizational commitment. Similarly, Yang (2011) in his study conducted on a sample of 172 restaurant employees in Taiwan revealed that HRM practices tell that empowerment was positively and directly related to affective commitment.…”
Section: E Empowerment and Organizational Commitmentsupporting
confidence: 48%
“…Empowerment has been defined in several different ways due to varied definitions in the literature. Kuo et al, (2010) viewed that employee empowerment approaches can vary among organizations in different countries or even those in the same industry working on dissimilar business models. Michailova (2002) indicates that empowerment refers to the degree which employees are encouraged to make the decisions related to his work without taking the consultation of their managers.…”
Section: E Empowerment and Organizational Commitmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Our second hypothesis is also supported with p. value of 0.000 and T. value of 7.924 which establishes a significant and positive relationship of EC with organizational performance. Extensive studies have been carried out on the topic, and our results are consistent with the results of Kuo et al (2010);Nishii, Lepak, and Schneider (2008) and Samad (2013). We conclude that in the business environment of KP which is plagued by many logistical and supply chain bottlenecks, it is imperative that a strongly committed employee works for the organization who can take the extra step to cover for the supply chain deficiencies through personal interaction and commitment with the organization.…”
Section: Discussionsupporting
confidence: 86%
“…In other words, an employee with high level of EC will own the values and goals of the organization and will put greater efforts to achieve them. Kuo, Ho, Lin, and Lai (2010) argue that high employee commitment will result in employee achieving greater independence, swiftly develop core competencies and tend to be more accepting of tasks beyond their job description. All these attributes help organization achieve greater efficiencies and effectiveness in goal attainment.…”
Section: Literature Reviewmentioning
confidence: 99%